2021
DOI: 10.21203/rs.3.rs-225668/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Among Caregivers Towards Pressure Ulcer in Spinal Cord Injury at Rehabilitation Center in Bangladesh

Abstract: Study design: A quantitative cross-sectional survey study. Objective To determine the knowledge, attitude and practice (KAP) among caregivers regarding prevention and care of pressure ulcer in patients with spinal cord injury and relationship between KAP. Setting: Centre for Rehabilitation of Paralysed, Dhaka, Bangladesh. Methods A descriptive correlational design with modified semi-structured questionnaire implemented through convenient sampling procedure. McDonald’s standard of learning outcome measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…In addition, findings in the current study revealed that majority of 67.8% of the respondents had adequate knowledge of pressure ulcers prevention strategies. This is also in line with similar studies which reported adequate knowledge of pressure ulcers prevention strategies (Mäki-Turja-Rostedt et al, 2021;Tharu et al, 2021). However, the finding is not consistent with previous research where there was poor knowledge of prevention strategies among the respondents (Fletcher & Hall, 2020;Halász et al, 2021;Khojastehfar et al, 2020;Saranasinghe & Seneviratne, 2021;Sen, 2020;Sengul & Karadag, 2020).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, findings in the current study revealed that majority of 67.8% of the respondents had adequate knowledge of pressure ulcers prevention strategies. This is also in line with similar studies which reported adequate knowledge of pressure ulcers prevention strategies (Mäki-Turja-Rostedt et al, 2021;Tharu et al, 2021). However, the finding is not consistent with previous research where there was poor knowledge of prevention strategies among the respondents (Fletcher & Hall, 2020;Halász et al, 2021;Khojastehfar et al, 2020;Saranasinghe & Seneviratne, 2021;Sen, 2020;Sengul & Karadag, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Study on 253 nurses' knowledge and practices towards pressure ulcer prevention in Medical College Hospital, Kolkata reported that participants' overall knowledge towards pressure ulcer prevention was poor (Sen, 2020). However, a study on knowledge, practice, and perceived barrier of pressure ulcer prevention among 220 nurses in a public hospital in Selangor revealed that majority of respondents had adequate knowledge (95.0%) of PUs prevention (Tharu et al, 2021). Also a study on knowledge, attitude and practice among caregivers towards pressure ulcer in spinal cord injury at rehabilitation center in Bangladesh found that knowledge of PU prevention was moderately high in the majority 73.2% of the participants (Mäki-Turja-Rostedt et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Degree in Rehabilitation Science at the University of Dhaka, Bangladesh. The authors state that the manuscript “Caregivers' Knowledge, Attitude, and Practice towards Pressure Ulcer in Spinal Cord Injury at Rehabilitation Center in Bangladesh” has been previously published as a preprint [ 40 ].…”
Section: Disclosurementioning
confidence: 99%